TOPICS OF PEACEFUL COEXISTENCE IN FOREIGN SATELLITE CHANNELS DIRECTED IN THE ARABIC LANGUAGE: (A Research Drawn from Master Thesis) - Karim, Maryam Mohsen; Falhi, Mohammed Jasim (ALBAHITH ALALAMI, 2019)
This research deals with issues of peaceful coexistence in foreign satellite channels directed in the Arabic language, trying to get acquainted with the most prominent of these topics dealt with the programs subject to analysis and the method of dealing with them and the most used journalistic arts in that. The research adopted the descriptive approach and the method of content analysis for the purpose of studying the research community represented by the program «Shabab Talk» “Youth Talk” in the German channel Deutsche Welle (DW) and the program «Beina Sam wa Amar» “between Sam and Ammar” in the American free channel, by designing the content analysis form to subject the sample of analysis represented by (50) episodes of both programs. The form included a number of major and minor categories. It, moreover, included content analysis with categories of (What was said?); and shape analysis with categories of (How was it said?). The research included three aspects (methodological, theoretical, and applied).